Desire for Parenthood in Context of Other Life Aspirations Among Lesbian, Gay, and Heterosexual Young Adults - Tate, Doyle P.; Patterson, Charlotte J. (Frontiers in Psychology, 2019)
Research has established that sexual minority young adults generally report fewer desires and fewer expectations for parenthood than do their heterosexual peers. Little is known, however, about other desires and expectations. Is parenthood the only domain in which lesbian and gay individuals report fewer desires and expectations than their heterosexual peers? Or do lower aspirations among lesbian and gay adults about parenthood also occur in other domains, such as marriage and work? In this study, we explored a variety of desires and expectations for the future among lesbian, gay, and heterosexual young adults. Participants for this internet survey were recruited via social media, and included 368 childless cisgender young adults (211 lesbian or gay, 157 heterosexual) living in the United States. There were three main findings. First, while lesbian/gay individuals were less likely than heterosexual participants to express desire for parenthood, desires in the other future domains did not vary across sexual orientation. Lesbian/gay participants were as likely as heterosexual individuals to desire marriage, friendships, and community connections, as well as career and economic success. Results for expectations were, however, very different. Lesbian/gay participants were less likely than heterosexual individuals to expect that they would marry, become parents, feel connected to a community, achieve meaningful careers, live in their ideal housing, or that they would attain financial stability. Thus, although desires were largely unrelated to sexual orientation, many expectations were strongly linked to it. Lesbian and gay individuals were also far more likely than their heterosexual peers to desire future goals that they did not expect to achieve. Overall, for lesbian/gay young adults, low parenthood aspirations were part of a general pattern of low expectations (though not reduced desires) across a number of life domains.